2017
DOI: 10.1111/bpa.12468
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive genetic characterization of rosette‐forming glioneuronal tumors: independent component analysis by tissue microdissection

Abstract: A rosette-forming glioneuronal tumor (RGNT) is a rare mixed neuronal-glial tumor characterized by biphasic architecture of glial and neurocytic components. The number of reports of genetic analyses of RGNTs is few. Additionally, the genetic background of the unique biphasic pathological characteristics of such mixed neuronal-glial tumors remains unclear. To clarify the genetic background of RGNTs, we performed separate comprehensive genetic analyses of glial and neurocytic components of five RGNTs, by tissue m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Previous reports have indicated that the incidence of an FGFR1 mutation is 5.2%-6.7% in PA, 1,10 36.4% in DNT, 20 10% in oligodendroglioma, 20 and 46.2%-50% in rosette-forming glioneuronal tumor. 5,14 Our results suggest that FGFR1 mutation is also observed in pediatric and young adult cases of DA and PMA. All 4 cases harboring an FGFR1 mutation in our study were located in the thalamus and hypothalamus, which is consistent with previous reports of PA. 10 Although the FGFR1 mutation is associated with a poor prognosis in PA, 1 our cases had a significantly different outcome, suggesting clinical heterogeneity with respect to the FGFR1 mutation.…”
Section: Clinical Characteristics Of Lggs With An Fgfr1 Mutationmentioning
confidence: 51%
“…Previous reports have indicated that the incidence of an FGFR1 mutation is 5.2%-6.7% in PA, 1,10 36.4% in DNT, 20 10% in oligodendroglioma, 20 and 46.2%-50% in rosette-forming glioneuronal tumor. 5,14 Our results suggest that FGFR1 mutation is also observed in pediatric and young adult cases of DA and PMA. All 4 cases harboring an FGFR1 mutation in our study were located in the thalamus and hypothalamus, which is consistent with previous reports of PA. 10 Although the FGFR1 mutation is associated with a poor prognosis in PA, 1 our cases had a significantly different outcome, suggesting clinical heterogeneity with respect to the FGFR1 mutation.…”
Section: Clinical Characteristics Of Lggs With An Fgfr1 Mutationmentioning
confidence: 51%
“…Some alterations are pathognomonic for a tumor entity as SLC44A1‐PRKCA fusion gene for PGNT ; others are associated with two or more entities, as FGFR1 mutations associated at least with DNET, rosette forming glioneuronal tumor and pilocytic astrocytoma . It seems crucial to put our Case 1 into the molecular context of glioneuronal tumors . No fusions were detected involving PRKCA, BRAF , FGFR1, FGFR2, FGFR3 , MYB1 or MYBL1 genes although those genes were present in the capture panel of the TruSight RNA fusion kit.…”
Section: Discussionmentioning
confidence: 95%
“…The FGFR1 gene on chromosome 8p11.23 has emerged as a recurrently altered oncogene in a diverse spectrum of primary glial and glioneuronal tumor entities including DNT [ 31 , 33 , 34 , 40 , 41 ], RGNT [ 14 , 19 , 22 , 36 ], EVN [ 38 ], pilocytic astrocytoma [ 3 , 18 , 27 , 34 , 44 ], high-grade astrocytoma with piloid features [ 2 , 32 ], and H3 K27M-mutant diffuse midline glioma [ 24 ]. Notably, FGFR1 alterations are not commonly found in IDH-wildtype glioblastoma in adults, IDH-mutant astrocytoma, IDH-mutant and 1p/19q-codeleted oligodendroglioma, H3.3 G34-mutant diffuse hemispheric glioma, ganglioglioma, polymorphous low-grade neuroepithelial tumor of the young (PLNTY), papillary glioneuronal tumor, myxoid glioneuronal tumor, multinodular and vacuolating neuronal tumor, diffuse leptomeningeal glioneuronal tumor (DLGNT), central neurocytoma, and ependymomas of any location or subtype [ 5 , 6 , 8 , 9 , 16 , 17 , 23 , 24 , 26 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%